2013
DOI: 10.2134/agronj2012.0486
|View full text |Cite
|
Sign up to set email alerts
|

Stover Management and Nitrogen Fertilization Effects on Corn Production

Abstract: The incorporation of crop stover into the soil improves soil fertility and crop productivity by increasing C sequestration and reducing the emission of greenhouse gases among other parameters. Interactions between crop stover management and N fertilization could help to improve C sequestration while increasing productivity. The objective of this study was to evaluate the impact of incorporating or removing corn (Zea mays L.) stover, in combination with different N fertilization rates (0, 100, 200, and 300 kg N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
(49 reference statements)
1
9
0
Order By: Relevance
“…These amounts of available N were similar to those reported in other studies in the Ebro Valley [7,8,66,67]. Thus, the tested VIs enabled the spatial characterization of N status and were able to assess crop performance even under low-N stress [68].…”
Section: Vegetation Indices Spad and Plant Height Responses To N Ratsupporting
confidence: 86%
See 2 more Smart Citations
“…These amounts of available N were similar to those reported in other studies in the Ebro Valley [7,8,66,67]. Thus, the tested VIs enabled the spatial characterization of N status and were able to assess crop performance even under low-N stress [68].…”
Section: Vegetation Indices Spad and Plant Height Responses To N Ratsupporting
confidence: 86%
“…The study area is characterized by a semiarid climate with low precipitation (192 mm) and high average temperature (19.1 • C) during the maize growing period [7]. The summer of 2015 (June-August period) was hotter than the same period of 2014 (1.0, 1.5 and 2.1 • C for minimum, mean and maximum temperatures, respectively).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the Foggia experiment (Figure a), the incorporation of crop residues lowered yield because of the poor mineralization and strong N immobilization due to arid climate and the low soil N status (Maiorana, ). Mineral N fertilizer application did not increase yields at Almacelles even though SOC concentrations were sufficient, possibly due to the short duration of the experiment and the arid climate (Biau et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Warmer soil temperatures associated with stover removal likely provided more favorable conditions for corn germination, growth, and grain production (Kaspar et al, 1990;Sims et al, 1998;Blanco-Canqui & Lal, 2007;Sindelar et al, 2013;Halvorson & Stewart, 2015). In contrast, some irrigated corn studies have reported that stover removal did not affect yield (Biau et al, 2013;Huang et al, 2013;Kenney et al, 2013), and progressive yield declines have been found in rainfed corn production sites when stover was removed (Wilhelm et al, 2004;Blanco-Canqui & Lal, 2007).…”
Section: Crop Productivitymentioning
confidence: 99%